An effort‐based index of beta diversity. Issue 3 (30th January 2013) - Lazarina, Maria; Sgardeli, Vasiliki; Kallimanis, Athanasios S.; Sgardelis, Stefanos P.
Summary: Beta diversity provides a link between species diversity in a region to species diversity within sites. Many metrics have been proposed for its estimation each reflecting a different aspect of the phenomenon. Many of them are more informative of the variation in alpha diversity among samples and the sampling effort (number of sampling units) rather than of the species assemblage differentiation. Here, we propose an index based on the sampling effort needed to fulfil a certain criterion and accounts for the relationship between the initial slope of the species accumulation curve and mean alpha diversity. For defining the index, we consider a set of n samples with S ( n ) species among R ( n ) total occurrences. The shared species occurrences are I ( n ) =  R ( n ) −  S ( n ). The proposed new index ( N* ) is defined as the point, in terms of n, where I ( n ) crosses S ( n ). Samples taken beyond that point ( N* ) contribute, cumulatively, more to the shared occurrences rather than to new species. For the estimation of N*, we provide the R function 'Nstar' based on the specaccum function in the vegan package. We tested the properties of N* on simulated datasets with known community assembly patterns and on a dataset of plant diversity of Greek Natura 2000 protected areas. N* is not mathematically confounded with alpha or gamma diversity. It depends on the relationship between gamma and alpha (Whittaker's index) but, furthermore, it reflects the variation in species occupancies. Thus, if a number of random samples, sufficient for the reliable estimation of mean alpha diversity and the species accumulation curve, is collected, N* converges to a value that does not change by the inclusion of more samples from the same region. N* depends primarily on the proportion of new species expected in each next sample. N* declines with nestedness in community structure, while it increases with species turnover. This holds for plant diversity of Greek Natura 2000, where N* exhibited lower values in island compared to continental regions reflecting the increased nestedness of island communities.